ATTENDANCE QUESTIONS TO ENHANCE LEARNER ENGAGEMENT IN ONLINE CLASSES - Ramadhani, Farah (J-ELLiT (Journal of English Language, Literature, and Teaching), 2023)
The present study was action research to overcome the disengagement among EFL student teachers by using attendance questions. The participants included 37 student teachers who attended the ELT Methods course in Google Classroom. In the second half of the semester, they responded to attendance questions at the beginning of each session to increase their motivation and improve their engagement in learning. To collect the data, the teacher educator kept reflective journals and conducted participatory observation. The student teachers completed a questionnaire on learner engagement, followed by semi-structured interviews. The results indicated the intervention effectively revived the student teachers’ engagement. The improvement occurred in the behavioral, affective, and cognitive areas, but the affective engagement was the most favorably affected. The reasons for the improved engagement from the student teachers’ perspectives provided compelling insight into the connection between the attendance questions, motivation, and learner engagement. Based on these findings, the implication for the EFL teacher training was presented.